Improvement of The Photostability of Nimodipine by Using Liquisolid Compacts Technique - Mustafa E. Khazim,; Hamid J. Hasan,; Noor M. Hanoon ,; Hussein A. Hussein Al-Sa’idy , (University of Thi-Qar Journal of Science, 2021)
Liquisolid compacts are one of the modern drug formulation  techniques used for drug formulation for several objectives including protection against photosensitivity. This study evaluates the photoprotective effect of the liquisolid compact technique on a calcium channel blocker antihypertensive drug, nimodipine, which is considered a photosensitive drug model. Liquisolid compact tablets of nimodipine were prepared from; Avicel PH-102 as a carrier material, (colloidal silicon dioxide, Cab-O-sil,  and titanium dioxide as coating materials), croscarmellose sodium (CSS), sodium starch glycolate (SSG), crospovidone (CP) as super disintegrants, and propylene glycol as the liquid vehicle. However, the ratio of carrier to coating materials was kept constant in all formulations at 35:1. This ratio was chosen after testing the ratios 15:1, 20:1, 25:1, 30:1 and 35:1. The feasibility of the prepared liquisolid systems was also evaluated for first; the pre-compression and post-compression characteristics. Second, the possible drug-excipients interaction using FT-IR. Third, the photostability of Nimodipine in pure form, conventional tablets, and in the prepared liquisolid tablets through irradiation with a light dose of 0.55 W/m2/h visible light, 50 W/m2/h UVA and 0.27 W/m2/h UVB for 12 h in order to estimate the effect of coating material type on Nimodipine stability especially in the prepared liquisolid formulations. The results showed that all of the prepared liquisolid tablets showed satisfactory properties regarding pre and post-compression properties. Interestingly, the FTIR spectra study ruled out any interaction between nimodipine and excipients in the prepared liquisolid tablets. Besides, all of the prepared liquisolid tablets had shown a superior drug.